2016 American College of Rheumatology/European League Against Rheumatism Criteria for Minimal, Moderate, and Major Clinical Response in Juvenile Dermatomyositis: An International Myositis Assessment and Clinical Studies Group/Paediatric Rheumatology International Trials Organisation Collaborative Initiative. Issue 5 (6th April 2017) - Rider, Lisa G.; Aggarwal, Rohit; Pistorio, Angela; Bayat, Nastaran; Erman, Brian; Feldman, Brian M.; Huber, Adam M.; Cimaz, Rolando; Cuttica, Rubén J.; de Oliveira, Sheila Knupp; Lindsley, Carol B.; Pilkington, Clarissa A.; et al.
Abstract : Objective: To develop response criteria for juvenile dermatomyositis (DM). Methods: We analyzed the performance of 312 definitions that used core set measures from either the International Myositis Assessment and Clinical Studies Group (IMACS) or the Paediatric Rheumatology International Trials Organisation (PRINTO) and were derived from natural history data and a conjoint analysis survey. They were further validated using data from the PRINTO trial of prednisone alone compared to prednisone with methotrexate or cyclosporine and the Rituximab in Myositis (RIM) trial. At a consensus conference, experts considered 14 top candidate criteria based on their performance characteristics and clinical face validity, using nominal group technique. Results: Consensus was reached for a conjoint analysis–based continuous model with a total improvement score of 0–100, using absolute percent change in core set measures of minimal (≥30), moderate (≥45), and major (≥70) improvement. The same criteria were chosen for adult DM/polymyositis, with differing thresholds for improvement. The sensitivity and specificity were 89% and 91–98% for minimal improvement, 92–94% and 94–99% for moderate improvement, and 91–98% and 85–86% for major improvement, respectively, in juvenile DM patient cohorts using the IMACS and PRINTO core set measures. These criteria were validated in the PRINTO trial for differentiating between treatment arms for minimal and moderate improvement ( P  = 0.009–0.057) and in the RIM trial for significantly differentiating the physician's rating for improvement ( P  < 0.006). Conclusion: The response criteria for juvenile DM consisted of a conjoint analysis–based model using a continuous improvement score based on absolute percent change in core set measures, with thresholds for minimal, moderate, and major improvement.